Evaluation of Water Quality of Water Storage Cisterns in Apartments (Case Study of Kermanshah City) - Mohana Faraji; Milad Roshanbas; Mitra Javan (آب و فاضلاب)
Water quality control in terms of solutes, color, taste, odors and existing bacteria is of vital importance from a health point of view. Water quality problems in storage facilities can be classified as microbiological, chemical and physical. Water stagnation in many storage facilities is probably the most important factor associated with declining water quality. Accumulation of sediment in cisterns leads to potential water quality problems and increased demand for disinfectants, microbial growth, water turbidity and chlorine depletion. To investigate the safety of the stored water, further research is needed. Requirements outlined in Issue Sixteen of the Iranian National Building Code emphasize specifications related to water storage tanks. In this research, the field observation method was employed to investigate the requirements of the national building regulations for 105 cisterns of apartments in Kermanshah city in two types of polyethylene and galvanized steel. Additionally, the factors affecting the problems that have been created inside the cisterns of the apartments have been evaluated. The results showed that in 8% of the apartments, the subscribers used direct pumping, which contravenes the established requirements. Furthermore, in 26% of the cisterns, the amount of residual free chlorine is lower than the recommended amount specified in Publication 1053 of the National Standard of Iran. In 7% of the cisterns, the water temperature is higher than the value suggested in the English standard (BS 8558:2015). All cisterns are not equipped with warning pipes, overflow pipes, drain pipes, or vent pipes. Rust was clearly seen inside the galvanized steel cisterns. There is accumulated sediment at the bottom of all cisterns. In 86% of cisterns with a volume of more than 1000 liters, water stagnation occurs due to the inlet and outlet being located on the same side. Therefore, legal follow-ups and periodic visits to the cisterns of buildings are essential.